Dialectical Variation in the Syntax of Coordination and Subcoordination in Western Akkadian of the El-Amarna Period - Hayes, John Lewis (1984)
Ph.D. diss.; Order No.. DA8420184. Cf. DissAbstr 45 (1984) 1738-A.